Erythrocyte membrane ATPase activity in Sickle cell crisis - Rath, Debapriya; Rathore, Sudama; Verma, Neha Rani; Tirkey, Neelam B; Patra, Pradeep Kumar (Asian Journal of Medical Sciences, 2017)
Background: Sickle cell disease is a genetic disease caused by a point mutation in the beta globin gene on chromosome 11 leading to the substitution of valine in place of glutamic acid in beta subunit of globin molecule. The vaso-occlusive crisis, or sickle cell crisis, is a common painful complication of sickle cell disease in adolescents and adults. Many studies have suggested the alteration in intracellular concentration of various ions associated with sickle cell disease. Aims and Objectives: This study aims to evaluate the activity of red blood cell membrane ATPase activity of sickle cell crisis patients in comparison to sickle cell patients in steady state. Material and Methods: Twenty patients of sickle cell crisis were included in the study. Twenty sickle cell patients in steady state were also registered who served as controls. The RBC Membrane ATPase activity were estimated and expressed as μmol of Pi/μg of protein/hour. Results: The activity of membrane ATPase were found to be significantly high in patients of sickle cell crisis in comparison to steady state ones. Conclusion: Membrane ATPases play a crucial role in the pathophysiology of sickle cell crisis. This study can be a based upon for future studies to understand the pathophysiology of sickle cell crisis and development of diagnostic and treatment modalities for the same. Asian Journal of Medical Sciences Vol.8(5) 2017 27-30